Preparation and Properties of Antifreeze Rewarming Hydrogel Dressings - Meng Yan; Xiaorong Dong; Jingjing Sun; Yijun Liu; Shengchao Yang; Xing Tian; Shuang Zheng; Lisha Yin; Yanan Fu; Dongmei Li; Lin Cui; Gang Li; et al. (Advanced Materials Interfaces)
Abstract The Hydrogel wound dressing with good rewarming property, anti‐freezing property, and adhesion property has important practical significance in medical care for the first and second grade frostbite. The ears, hands, mouth, and nose of field workers on duty and training high cold region are prone to frostbite due to long‐term exposure to in severe cold. Therefore, rapid rewarming of wound surface is the key to the treatment of frostbite. In this paper, antifreeze and rewarming are achieved by photothermal conversion materials and quaternary ammonium salts. Herein, the PAM/CS/MXene30/Betaine5/AgNPs200(PCM30B5A200) hydrogel based on chitosan (CS) and acrylamide (AM) is designed and fabricated by thermally initiated free radical polymerization. The dressing has excellent rewarming properties, anti‐freezing properties, tensile properties, repeatable self‐adhesion and antibacterial properties. In this system, hydrogels are mainly cross‐linked by hydrogen bonds between CS and AM. Betaine is added to the material to make the hydrogel have good freeze‐resistance and flexibility at −24 °C, and can be combined with AgNPs and MXene, to achieve a triple antibacterial. The PCM30B5A200 hydrogel reached the rewarming temperature of 40.5 °C at 9 min. PCM30B5A200 multifunctional hydrogels have good application value in the first and second grade frostbite wounds.